An Analysis of Primary and Secondary Slang Used in The Movie “Plane” by Jean François Richet (Humanis, 2026)
This study is entitled “An Analysis of Primary Slang and Secondary Slang Used in The Movie “Plane” by Jean- Francois Richet. This is a study aimed at analyzing the use of primary and secondary slang in the film "Plane," directed by Jean-François Richet. The methodology used in this study involves collecting data using a structured descriptive approach and analyzing the data using Chapman (2007) as a theoretical framework. The analysis showed that secondary slang words were more common in the film, with 16 (73%) occurrences, compared to 6 (27%) occurrences of primary slang. This study highlights the importance of primary and secondary slang in character interactions and narrative authenticity in the film. The analysis of the film "Plane" and Chapman's slang language theory has enhanced our understanding of language's contribution to cinematic storytelling.
Keywords: slang; types; movie